Expectations, family networks, and emigration a study of Filipino decision-making. [article]. - Sycip, Lynna-Marie
his study examined the Filipino migration system involving Ilocos Norte, Metro Manila and the United States. Baseline interviews were conducted with 1,744 adults from Ilocos, with a follow-up 30 months later to measure actual and intended migration behavior. It later focused on 177 US movers and 437 actual and intended Philippine stayers and movers within the Philippines. These were further given a 28-item scale of values previously associated with migration. Data identified network support variables as the strongest predictor for migration behavior, that is, that US movers had relatives in the US to provide motivation, information, support and auspices to the Filipino imigrant. Such emphasized the Filipino's strong reliance on the family network and kinship ties. The study concludes with the suggestion to include cultural dimensions in models of migration decision-making.